Multidrug Resistant Transfusion Vivax Malaria - Emiliana Tjitra; Bondan Lukito; Suriadi Gunawan (Indonesian Pediatric Society Publishing House, 2018)
A 17-day-old premature baby girl had received a blood exchange transfusion because of hyperbilirubinemia and got another blood transfusion because of severe anemia on day 45. The diagnosis of transfusion vivax malaria was made when she had severe anemia again on day 78. The most predominant clinical signs were fever, anemia, hepatosplenomegaly, and thrombocytopenia. Treatment with chloroquine 25 mg base/kg BW showed resistance at RIII level on a 7 -day follow up. She was retreated. with quinine 10 mg salt/age in month divided in 3 doses/day for 7 days. lt also showed resistance at late RI level on day-30. Then she was retreated with quinine 15 mg  salt/age in month divided in 3 doses/day for 7 days and still showed resistance at late Rl level on day 32. Finally she was treated with quinine 10 mg salt/kg BW /dose, tid for 7 days which was effective. During the course of treatment, no adverse reactions were found clinically. This malaria case was transfusion vivax malaria resistant to choloroquine at R III level and to quinine at late RI level. Quinine 10 mg salt/BW I dose tid for 7 days was effective and safe for infants.